Réponses

2014-02-05T19:44:23+01:00
A. f(x)= (x-1)²-(2-x)(x-1)
        = x²+1-(2xx+2x-1-xxx-xx-1)
        = x²+1-2x+2+x²-2x
        = 2x²-4x+3

Il y doit y avoir une érreure, mais je ne vois pas où.

b. f(x)= (x-1)²-(2-x)(x-1)
        = (x-1)[(x-1)-(2-x)]
        = (x-1)[x-1-2+x]
        = (x-1)(2x-3)

c. Je choisis la forme 2 = 2x²-5x+3
    f(3/2)= 2x(3/2)²-5x3/2+3
           = 4,5-7,5+3
           = 1

    f( \sqrt{3} )= 2x( \sqrt{3} )²-5x \sqrt{3} +3
           = 6-8,6+3
           = -1,6

d. Désoler je ne me rapelle plus comment on fais :/